UHI effects and strategies to improve outdoor thermal comfort in dense and old neighbourhoods. (October 2017) - Evola, G.; Gagliano, A.; Fichera, A.; Marletta, L.; Martinico, F.; Nocera, F.; Pagano, A.
Abstract: Modelling techniques have received growing attention as a tool to investigate the thermal comfort within a city, on the basis of which decision makers can set-up appropriate mitigation strategies. This research aims at studying the effectiveness of strategies for reducing the urban heat island-associated effects in dense and old neighborhoods considering, in particular, green roofs, cool roofs, cool pavements, green areas and urban renewal actions. Computer simulation was selected as the major methodology in this research; ENVI-met software was used under different scenarios for a case study consisting in an old neighborhood in the city of Avola. The investigation focused on evaluating the efficacy of each strategy for a condition corresponding to a typical summer heat wave. The results highlight that the cool pavements allow relevant improvements at the height of 1.50 m, with a temperature decrease up 1.15°C, whereas the other scenarios, given the relatively high density of the buildings, are able to improve outdoor conditions only at higher elevations. Reported results represent a guideline for the choice of UHI mitigation method that can help stakeholders involved in new urban assessment of old neighborhoods in Mediterranean climate.